Safety, Tolerability, and Effect of Nusinersen Treatment in Ambulatory Adults With 5q-SMA - Elsheikh, Bakri; Severyn, Steven; Zhao, Songzhu; Kline, David; Linsenmayer, Matthew; Kelly, Kristina; Tellez, Marco; Bartlett, Amy; Heintzman, Sarah; Reynolds, Jerry; Sterling, Gary; Weaver, Tristan; et al. (Frontiers in Neurology, 2021)
Objective: To determine the safety and tolerability of nusinersen treatment in ambulatory adults with spinal muscular atrophy (SMA) and investigate the treatment effect on muscle strength, physical function, and motor unit physiology. Methods: Individuals aged 18 years or older with genetically confirmed 5q SMA, three or more copies of the SMN2 gene, and the ability to ambulate thirty feet were enrolled. Safety outcomes included the number of adverse events and serious adverse events, clinically significant vital sign or laboratory parameter abnormalities. Outcome assessments occurred at baseline (prior to the first dose of nusinersen) and then 2, 6, 10, and 14 months post-treatment. Results: Six women, seven men (mean age: 37±11, range: 18-59 years) were included for analyses. The most common side effects were headache and back pain, but overall procedures and treatments were well tolerated. No serious adverse events were reported. Maximal Voluntary Isometric Muscle Contraction Testing (MVICT) and 6-minute walk test (6MWT) both showed overall stability with significant increases at 2, 6, and 10 months for the 6MWT. More consistent significant treatment effects were noted on the Hammersmith Functional Motor Scale Expanded, SMA-Functional Rating Scale, and forced vital capacity. Treatment resulted in progressively increased ulnar compound muscle action potential and average single motor unit potential amplitudes, but motor unit number estimation remained stable. Conclusions: Nusinersen treatment is safe and well-tolerated in ambulatory adults with SMA. Treatment resulted in improved motor function and electrophysiological findings suggest that this improvement may be occurring via improved motor unit reinnervation capacity.